2019
DOI: 10.1080/03055698.2019.1651692
|View full text |Cite
|
Sign up to set email alerts
|

Peer-to-peer dialogue about teachers’ written feedback enhances students’ understanding on how to improve writing skills

Abstract: Academic writing is a complex competence in higher education. To develop this competence, teachers' written feedback is vital, especially if it contains feed-up, feedback and feedforward information. However, academic writing does not always improve after provision of written feedback. The purpose of this study was to explore if peer-to-peer dialogue between students about teachers' written feedback does enhance students' understanding of written feedback. Sixtythree second-year university students participate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…This particular finding supports the current argument that learners should be active in the process (Henderson et al, 2019). It is also in line with Schillings et al (2019) that learner-learner dialogue enhances students' understanding of teacher feedback.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…This particular finding supports the current argument that learners should be active in the process (Henderson et al, 2019). It is also in line with Schillings et al (2019) that learner-learner dialogue enhances students' understanding of teacher feedback.…”
Section: Discussionsupporting
confidence: 71%
“…Carless (2020) stated that teacher effective feedback should engage learners in interacting with teachers to establish mutual understandings and resolve dissonances resulting from feedback. Moreover, interaction is another means to improve students' comprehension of teacher feedback (Schillings et al, 2019).…”
Section: Students' Responses To Feedbackmentioning
confidence: 99%
See 2 more Smart Citations
“…Feedback intervention not only affects students but also affects pre-service teachers' motivation, which enhances their reflective thinking power (Çimen &Çakmak, 2020). Schillings et al (2020) also confirmed that teachers' provided feedback improved students' understanding of the assessment criteria (feedback) and offered suggestions for improvement (feed-forward). Written feedback from high-quality teachers was regarded as an essential criterion for improving students' motivation and understanding of how to improve their academic writing assignments.…”
Section: Conclusion and Discussionmentioning
confidence: 57%